Finite Element Analysis of the Gravity Davit Structure on MV. Sultan Hasanuddin with Variations Lifeboat Load Capacity - Jafar, Muhammad; Darwis, Darwis; Noegraha, Andi Dirga (Maritime Park: Journal of Maritime Technology and Society, 2025)
The purpose of this study is to measure the maximum support capacity of the Davit structure on MV. Sultan Hasanuddin using variations in lifeboat load capacity. Davits on ships function as tools used to raise or lower lifeboats on board. The method used in this study is a quantitative method employing the Finite Element Analysis (FEA) technique to determine the ultimate stress and maximum deformation occurring in the Davit structure of the MV. Sultan Hasanuddin due to loading effects. Based on simulation results with six variations of passenger loading, the maximum stress experienced by the Davit (Davit) of the MV. Sultan Hasanuddin was on the suspension block, specifically on the davit chain. It was found that the maximum passenger weight limit on the lifeboat that does not exceed the BKI allowable stress is 4,363 kg, or an additional load of 35% of the total passenger weight, with a maximum gravitational force acting on the lifeboat of 74,441 N on the davit structure.